Differential geometry of GLh(1|1) - Çelik, S (AMER INST PHYSICS, 2001)
We construct a differential calculus on the quantum supergroup GL(h)(1\1) and obtain the h-deformed superalgebra of GL(h)(1\1). (C) 2001 American Institute of Physics.
Keywords: QUANTUM GROUPS; CALCULUS; SUPERGROUPS; DEFORMATION; MATRIX; Physics